Emicizumab prophylaxis in severe hemophilia A with inhibitor: impact on quality of life and musculoskeletal outcomes - Wiharta, Fitri Primacakti; Saraswati, Made Citra; Abigail, Dina Clarisa Rumora; Chozie, Novie Amelia (Faculty of Medicine Universitas Indonesia, 2025)
Emicizumab has been acknowledged for its effectiveness in preventing bleeding in patients with hemophilia A developing inhibitors. This report examined the impact of emicizumab prophylaxis on health-related quality of life (HRQoL) and musculoskeletal outcomes in a 10-year-old male with severe hemophilia A and a high titer of factor VIII (FVIII) inhibitor, presenting with hemophilic arthropathy on the right knee and left elbow. He had been unable to walk and was previously treated on-demand with a plasma-derived FVIII concentrate. He received emicizumab prophylaxis for 16 months. HRQoL was evaluated using a hemophilia-specific questionnaire, while musculoskeletal outcomes were assessed using hemophilia early arthropathy detection with ultrasound (HEAD-US) and the hemophilia joint health score (HJHS). During treatment, no breakthrough bleeding occurred, and the patient regained the ability to walk. Emicizumab prophylaxis significantly improved in HRQoL, especially in physical health and sports and and school domains, aligning with bleeding rates, HEAD-US, and HJHS assessments.